Neodymium iron boron magnets and their manufacturing methods and applications
A controlled granular structure and multi-stage sintering process for neodymium iron boron magnets address the challenges of high-temperature performance and abnormal grain growth, enhancing magnetic properties and stability.
Patent Information
- Application Number
- JP2024539034
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-27
- Filing Date
- 2022-11-28
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2042-11-28
AI Technical Summary
Existing neodymium iron boron sintered magnets face challenges in maintaining high magnetic performance under high temperatures due to the use of scarce and costly dysprosium and terbium, which also lead to abnormal crystal grain growth and reduced magnetic field intensity, hindering miniaturization and lightweight device development.
A neodymium iron boron magnet composition with a controlled granular structure, including a triangular grain structure and specific atomic concentrations of CU, GA, and AL, along with a multi-stage sintering process to suppress abnormal grain growth and enhance magnetic properties.
The solution achieves high residual magnetic flux density (BR) and coercivity (HCJ) by ensuring uniform element distribution and preventing abnormal grain growth, resulting in improved magnetic performance and stability.
Smart Images

Figure 2025503524000001_ABST
Abstract
Description
Detailed Description of the Invention
[0001] This application claims priority to a prior application bearing patent application number 202111616641.6 and entitled "Neodymium iron boron magnet and its manufacturing method and application," filed with the State Intellectual Property Office of China on December 27, 2021. The above prior application is hereby incorporated by reference in its entirety.
[0002] [Technical field] The present invention belongs to the field of neodymium-iron-boron magnets, and more particularly to a neodymium-iron-boron based sintered magnet and its manufacturing method and applications.
[0003] [Background technology] Neodymium iron boron sintered permanent magnet materials are currently the permanent magnetic functional materials with the highest overall magnetic performance and the widest range of applications, and are known as the modern "king of magnets". They are an important supporting material for promoting the development of related fields such as energy and information. Since their appearance in the 1980s, neodymium iron boron sintered magnets have been widely used in many fields such as the automotive industry, medical equipment, electronic information, and aerospace due to their excellent magnetic performance and extremely high cost performance, and are an important support for the development of intelligent, miniaturized and lightweight magnets in related fields. In recent years, as the performance of neodymium iron boron sintered magnets has been increasingly improved, their application fields have also continued to expand.
[0004] Neodymium-iron-boron sintered permanent magnet materials must have high coercivity performance to ensure stable magnetic field output under high temperature conditions. Conventionally, heavy rare earth Dy / Tb raw materials are often added in the smelting process to improve the coercivity of magnets. Due to the small stock of heavy rare earth resources and high prices, large-scale utilization of heavy rare earth resources is not only not conducive to the sustainable mining and use of heavy rare earth resources, but also directly leads to a significant increase in the production and manufacturing costs of magnets. In addition, the addition of heavy rare earth metals reduces the remanence of magnets, further reducing the magnetic field strength provided by magnets to space, which is unfavorable to the weight and size reduction of related equipment.
[0005] In order to improve the performance of magnets and reduce the amount of heavy rare earths such as terbium and dysprosium, two-alloy technology, grain refinement technology, and grain boundary diffusion technology have attracted the attention of the industry. At present, grain refinement technology and grain boundary diffusion technology are the most widely applied technology, and grain refinement technology is used to obtain a relatively small particle size of jet mill powder by controlling the process parameters of the smelting and powder milling process, and then matched with the corresponding sintering system, ultimately achieving the purpose of controlling the refinement of magnet particle size, thereby reducing the defects of crystal grains inside the magnet and improving the coercive force of the magnet.
[0006] In grain boundary diffusion technology, a diffusion source containing terbium and dysprosium elements is coated on the surface of a magnet by a method such as dip coating or spray coating. The terbium and dysprosium elements diffuse into the inside of the magnet through the grain boundary phase, replacing Nd in the neodymium-rich phase at the grain boundary, and forming (Dy / Tb)2Fe around the main phase crystal grains. 14 B is formed, the anisotropy of the grain boundary is improved, and the coercive force is improved.
[0007] Grain refinement technology and grain boundary diffusion technology can be used alone or in combination. In the combined application, grain refinement technology determines the basis of the final performance of the magnet. When grain refinement technology is used, the magnet grain size is fine, the surface area of the main phase crystal grains increases, the surface energy increases, the activity becomes greater, and the adsorption of impurity elements C, S, O, and N is difficult to eliminate, not only degrading the performance, but also making it easy for abnormal grain growth to occur, further degrading the magnetic performance. The magnet has abnormally grown crystal grains, and the effect of grain boundary diffusion is also greatly reduced.
[0008] Patent document CN106252012A provides a split sintering method for preventing abnormal grain growth, which involves keeping the temperature at a constant temperature 20°C lower than the sintering temperature of a NdFeB magnet for 0-1 hour, then raising the temperature to the sintering temperature and keeping the temperature for 3-6 hours, naturally cooling to 700-800°C, and then raising the temperature to a temperature 0-20°C higher than the sintering temperature and keeping the temperature for 5-8 hours, thereby obtaining a magnet with fine grains and uniform density, realizing a high-performance NdFeB magnet with low heavy rare earth content, and preventing abnormal grain growth. Although the above split sintering process is used, the sintering temperature is high and the split keeping time is long under the condition of fine grain size, so there is still a risk of abnormal grain growth, and the overall sintering period is long, resulting in low mass production efficiency.
[0009] Summary of the Invention In order to improve the above technical problems, the present invention provides a high performance neodymium iron boron magnet, the magnet is R2(Fe,M) 14 The alloy includes main phase grains and a grain boundary phase having a B structure, the grain boundary phase including a bigrain boundary between two main phase grains and a triangular boundary formed by gaps between three or more main phase grains, in which M includes Cu, Ga, and / or Al, and R is at least one rare earth element including Nd.
[0010] According to an embodiment of the present invention, R includes Nd and further includes at least one selected from the rare earth elements Y, La, Ce, Pr, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and Sc.
[0011] According to an embodiment of the present invention, the average grain size of the main phase crystal grains of the magnet is 1.8 to 8 μm, preferably 2.5 to 6 μm. Within this grain size range, the magnet can obtain relatively good magnetic performance, if the grain size is smaller, less than 1.8 μm, the surface activity of the crystal grains will be greater, and impurity elements such as O / N will be more likely to be adsorbed, and the adsorbed impurity elements will be more difficult to remove, resulting in a decrease in performance, if the grain size is relatively large, more than 8 μm, the internal structural defects of the main phase crystal grains will increase, and the grain boundary phase will be relatively diluted, making it difficult to obtain a high-performance NdFeB magnet.
[0012] According to an embodiment of the present invention, the atomic concentration of Cu in adjacent main phase crystal grains is set to [Cu1], and the atomic concentration of Cu at the two-grain boundary is set to [Cu2], so that the relationship 1≦[Cu2] / [Cu1]<2 is satisfied.
[0013] According to an embodiment of the present invention, the triangular grain boundaries in the magnet include Cu-rich regions, the atomic concentration of Cu in the triangular grain boundaries is set to [Cu3], satisfying the relationship [Cu3] / [Cu1]≧2, the grain boundary phase of the Cu-rich regions is a non-magnetic phase, and when the content of the Cu-rich regions in the magnet is relatively high, the Br of the magnet is significantly reduced. In the triangular grain boundaries of the present invention, the regions where the concentration of Cu element satisfies [Cu3] / [Cu1]≧2 are defined as Cu-rich regions.
[0014] According to an embodiment of the present invention, the ratio of the area of the Cu-rich regions of the triangular grain boundaries to the total area of the grain boundary phase is <5%.
[0015] According to an embodiment of the present invention, the atomic concentration of Ga in adjacent main phase crystal grains is set to [Ga1], and the atomic concentration of Ga at the two-grain boundary is set to [Ga2], so that the relationship 1≦[Ga2] / [Ga1]<2 is satisfied.
[0016] According to an embodiment of the present invention, the triangular grain boundaries in the magnet include Ga-rich regions, the atomic concentration of Ga at the triangular grain boundaries is set to [Ga3] and satisfies the relationship [Ga3] / [Ga1]≧2, i.e., the regions at the triangular grain boundaries where the concentration of Ga element satisfies [Ga3] / [Ga1]≧2 are defined as Ga-rich regions, the grain boundary phase of the Ga-rich regions is a non-ferromagnetic phase, and preferably the ratio of the area of the Ga-rich regions at the triangular grain boundaries to the total area of the grain boundary phase is <5%.
[0017] According to an embodiment of the present invention, the atomic concentration of Al in adjacent main phase crystal grains is set to [Al1], and the atomic concentration of Al at the two-grain boundary is set to [Al2], so that the relationship 1<[Al2] / [Al1]<2 is satisfied.
[0018] According to an embodiment of the present invention, the triangular grain boundaries in the magnet include Al-rich regions, the atomic concentration of Al at the triangular grain boundaries is set to [Al3] and satisfies the relationship [Al3] / [Al1] ≧ 2, i.e., the regions in the triangular grain boundaries where the concentration of Ga element satisfies [Al3] / [Al1] ≧ 2 are defined as Al-rich regions, the grain boundary phase of the Al-rich regions is a non-magnetic phase, and preferably the ratio of the area of the Al-rich regions of the triangular grain boundaries to the total area of the grain boundary phase is < 5%.
[0019] In the present invention, adjacent main phase crystal grains refer to main phase crystal grains adjacent to a two-grain grain boundary.
[0020] In conventional magnet manufacturing processes, Cu hardly penetrates into the main phase crystal grains, but is mainly present in the Nd-rich phase at the grain boundaries, improving hcj and improving irreversibility. However, if the Cu content is too high, it will result in a decrease in Br and Hcj performance. A small amount of Al occupies the 8j2 crystal position in the main phase crystal grains, refines the crystal grains, and most of the Al reduces the nodular distribution of the Nd-rich phase and B-rich phase at the grain boundaries, improving the wetting angle with the main phase and making the Nd-rich phase more uniformly distributed along the boundaries. A small amount of Ga is present in the main phase crystal grains, mainly concentrated at the grain boundaries, refines the crystal grains, and improves the wettability of the crystal grain surfaces. However, since the compound formed is a non-ferromagnetic phase, it is inevitable to reduce Br by adding Cu / Ga / Al, etc. Furthermore, these stable compounds were concentrated in the grain surface layer, inhibiting the substitution reaction of the grain surface layer component structure by heavy rare earth elements such as Dy / Tb in the diffusion process, which directly led to a significant decrease in the diffusion Hcj amplification.
[0021] According to an embodiment of the present invention, [Cu2] / [Cu1] is equal to or greater than 1 and less than 2, and more preferably 1.2 to 1.8. Within this range of atomic concentration ratio, Cu is distributed relatively uniformly in the main phase crystal grain surface layer and in the two grain boundaries, and Ga and Al also show the same regularity.
[0022] According to an embodiment of the present invention, the high-performance NdFeB magnet further contains transition metal elements such as Mn, Si, Zr, Ti, and Nb, and when the transition metal elements are concentrated in the grain boundary phase and have a distribution rule similar to that of Cu, Ga, and Al in the magnet, i.e., 1≦[Zr2] / [Zr1]<2, and / or 1≦[Ti2] / [Ti1]<2, and / or 1≦[Nb2] / [Nb1]<2, a high-performance magnet can be obtained. Wherein, [Zr1] represents the atomic concentration of Zr in adjacent main phase crystal grains, [Zr2] represents the atomic concentration of Zr at the two grain boundaries, [Ti1] represents the atomic concentration of Ti in adjacent main phase crystal grains, [Ti2] represents the atomic concentration of Ti at the two grain boundaries, [Nb1] represents the atomic concentration of Nb in adjacent main phase crystal grains, and [Nb2] represents the atomic concentration of Nb at the two grain boundaries.
[0023] According to an embodiment of the present invention, the high performance neodymium iron boron magnet is, at 100% by mass, 27-35% R, 0.8~1.2wt% B, 0 to 3.0 wt% Co, 0.1-0.6 wt% Cu, 0.1 to 0.8 wt% Ga, 0-1.0wt% Al, 60 to 72 wt% T; In the formula, R is at least one rare earth element including Nd, and T includes Fe and other transition metal elements as well as unavoidable impurity elements, the transition metal elements having the above-mentioned meanings.
[0024] According to an embodiment of the present invention, R includes Nd and further includes at least one selected from rare earth elements Y, La, Ce, Pr, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Sc. Preferably, the R is at least one of Nd, Y, Dy, Tb, Ho, La, Ce, of which the total mass of Dy, and / or Tb, and / or Ho is ≦5wt% of the total mass of the magnet, and the total mass of La, and / or Ce, and / or Y is ≦3wt% of the total mass of the magnet. If R in the magnet is too high, the neodymium-rich phase of the magnet increases and Br decreases, and if R is too low, a uniform and continuous Nd-rich phase for magnetic insulation of the main phase crystal grains cannot be formed in the magnet, and the Hcj and squareness of the magnet rapidly deteriorate. R2(Fe,M) composed of rare earth elements such as Pr, Dy, Tb, and Ho 14 The B-based main phase crystal grains have a lower magnetic polarization strength and a better anisotropy magnetic field than Nd, which significantly reduces the Br of the magnet, improves the Hcj, and ensures a high Br of the magnet, while using small amounts of heavy rare earth elements such as Dy, Tb, and Ho to improve the Hcj of the magnet, and their content in the total magnet components is ≦5wt%. Rare earth elements such as La, Ce, and Y have intrinsic magnetic properties significantly lower than Nd, are abundant in stock, and are inexpensive, so they can be added in small amounts, and their content in the total magnet components is ≦3wt%. Preferably, R includes Nd and Pr.
[0025] According to an embodiment of the present invention, the B content is 0.8 to 1.2 wt%, more preferably 0.87 to 1.05 wt%, and even more preferably 0.93 to 1.00 wt%. If the B content is too low, R will be relatively high, the ratio of the R-rich phase formed will be relatively high, and the volume ratio of the main phase crystal grains will be small, resulting in a low magnet Br and unstable Hcj and squareness of the magnet. If the B content is too high, the volume ratio of the B-rich phase will be significantly increased, significantly reducing the magnetic performance.
[0026] According to an embodiment of the present invention, Co occupies the position of Fe in the main phase crystal grains within a magnet, and the atomic magnetic moment of Co is smaller than that of Fe. The addition of Co reduces the Br of a magnet, and at the same time, the addition of Co has a significant effect on the corrosion resistance and temperature resistance of a magnet. Therefore, the Co content is 0-3.0wt%, and more preferably 0.5-2wt%. When the Co content is 0, the corrosion resistance and temperature coefficient are significantly deteriorated, but when the Co content is more than 3wt%, the Br is significantly reduced and Hcj is also obviously deteriorated. In addition, high Co increases the brittleness of a magnet, making it prone to processing cracks and resulting in a low product pass rate. In addition, Co is a strategic metal and is used in large quantities, so there is a very high requirement for a stable supply of raw materials.
[0027] According to an embodiment of the present invention, the Cu content is 0.1-0.6 wt%, and more preferably 0.2-0.5 wt%. If the Cu content is too high, the growth of crystal grains is suppressed and the grain boundary phase is amplified, reducing the volume ratio of the main phase crystal grains and lowering the Br of the magnet. If the Cu content is too low and no Cu is added, the main phase crystal grains and B-rich phase of the magnet will become relatively coarse, significantly reducing the magnetic performance of the magnet.
[0028] According to an embodiment of the present invention, the Ga content is 0.1-0.8 wt%, and more preferably 0.2-0.6 wt%. If the Ga content is too high, the growth of crystal grains is suppressed and the grain boundary phase is amplified, reducing the volume ratio of the main phase crystal grains and lowering the Br of the magnet. If the Ga content is too low and no Ga is added, the main phase crystal grains and B-rich phase of the magnet will become relatively coarse, significantly reducing the magnetic performance of the magnet.
[0029] According to an embodiment of the present invention, the Al content is 0-1.0 wt%, and more preferably 0.1-0.5 wt%. If the Al content is too high, the growth of crystal grains is suppressed and the grain boundary phase is amplified, reducing the volume ratio of the main phase crystal grains and lowering the Br of the magnet. If the magnet does not contain Al, the main phase crystal grains and B-rich phase of the magnet will become relatively coarse, significantly reducing the magnetic performance of the magnet.
[0030] According to an embodiment of the present invention, T includes Fe and other transition metal elements, as well as inevitable impurity elements. The other transition metal elements are, for example, Mn, Si, Zr, Ti, Nb, etc., and the inevitable impurity elements are, for example, elements such as C, S, O, N, etc. Preferably, T includes Fe and / or Ti.
[0031] The present invention further provides a method for producing the above-mentioned neodymium-iron-boron magnet, the method comprising the steps of: (a) a smelting process in which the components of the magnet are melted, cast, and cooled to form an alloy sheet; (b) a milling process in which the alloy sheet is crushed into alloy powder; (c) a press forming process in which the alloy powder is press-formed under the action of a magnetic field to obtain a billet; (d) a sintering process of sintering the billet, aging, and manufacturing the billet to obtain a NdFeB magnet.
[0032] According to an embodiment of the present invention, the smelting process of step (a) is a general technique in the prior art, for example, a spinning method is used to prepare an alloy sheet; exemplarily, the above step (a) is specifically a smelting process, in which the components of the above magnet are fully melted into alloy molten steel in a medium frequency induction smelting furnace in a vacuum or inert gas atmosphere according to the blending ratio of the target components, and then rapidly cooled to form an alloy sheet or alloy ingot; exemplarily, secondary cooling is performed.
[0033] According to an embodiment of the present invention, said step (b) is a milling process, specifically including coarse grinding and fine grinding, and preferably said coarse grinding is selected from hydrogrinding and / or medium grinding.
[0034] Preferably, the pulverization is performed by a jet mill. Preferably, the jet mill is performed in an inert gas atmosphere. Preferably, the inert gas is selected from nitrogen gas, helium gas, and the like.
[0035] In the present invention, the above-mentioned hydro-crushing, medium crushing or jet milling can be carried out by any of the known operations in the prior art.
[0036] According to an embodiment of the present invention, in step (b), after pulverization, the alloy powder is further screened by grading wheel screening, etc. Illustratively, the SMD grain size of the alloy powder is 1.8-8 μm, preferably 2.5-6 μm, and X90 / X10≦4.5. Wherein, SMD is the area average grain size, the smaller the SMD, the smaller the grain size of the powder particles, and the larger the SMD, the larger the grain size of the powder particles, X90 represents the grain size value corresponding to the cumulative distribution percentage reaching 90%, that is, all the grain sizes of the particles are equal to or smaller than this grain size, and the number of the particles larger than this grain size value is 0, and X10 represents the grain size value corresponding to the cumulative distribution percentage reaching 10%, that is, all the grain sizes of the particles are equal to or smaller than this grain size, and the number of the particles larger than this grain size value is 0, and X90 / X10 represents the grain size distribution of the powder, and the smaller the X90 / X10, the more concentrated the grain size distribution of the powder.
[0037] According to an embodiment of the present invention, in step (b), it is necessary to further add a lubricant during pulverization, and preferably, the lubricant is added both before and after the jet mill. Adding the lubricant before the jet mill can improve the flowability of the powder, adding the lubricant during the jet mill can improve the flowability and uniformity of the powder, and adding the lubricant after the jet mill can also improve the uniformity and flowability of the powder, facilitating uniform powder filling and pressing.
[0038] Preferably, the lubricant is selected from known reagents in the prior art and used in a known amount in the prior art group to achieve sufficient and uniform mixing of powder and ease of molding. Illustratively, the lubricant is selected from easily volatile organic solvents such as lipids or alcohols, for example zinc stearate. Illustratively, the amount of the lubricant added is 0.1-1 wt% of the total mass of the raw materials.
[0039] Preferably, further mixing is required after adding the lubricant, and the mixing time is preferably 1 to 6 hours.
[0040] The mixing according to the present invention can be carried out using methods known in the art, for example by mixing in a mixer.
[0041] According to an embodiment of the present invention, in step (c), the pressing is performed in a press die cavity.
[0042] According to an embodiment of the present invention, in step (c), it is necessary to perform alignment magnetization and molding with a magnetic field strength of 2 T or more before press molding, and either coil magnetization or pulse magnetization may be used.
[0043] According to an embodiment of the present invention, in step (c), after press molding, a reverse magnetic field is applied to perform demagnetization.
[0044] According to an embodiment of the present invention, in step (c), the compacted billet may be subjected to a cold isostatic press to further increase the billet density.
[0045] According to an embodiment of the present invention, in step (d), the billet is further heat-treated before the sintering process, the heat treatment temperature is 100-950°C, preferably 150-900°C, and the heat-treatment warming time is 60-120min, and the heat treatment temperature is 3-6 stages, the heat treatment temperature of each stage may be the same or different, the heat-treatment time may be the same or different, and the heat treatment stage may be performed in an inert gas or in a vacuum state. Exemplary, the heat treatment temperature is 4 stages, and is 100-200°C, 200-550°C, 550-700°C, and 700-950°C, respectively.
[0046] According to an embodiment of the present invention, in step (d), the sintering process has three or more sintering heat-holding stages and pre-sintering heat-raising stages, illustratively 3 to 10 stages, for example 3, 4, 5, 6, 7, 8, 9 or 10 stages, the temperature of the sintering heat-holding stage is 950 to 1200°C, preferably 980 to 1070°C, the heat-holding time of each stage is 20 to 120 min, the heat-holding temperature of each sintering process may be the same or different, the heat-holding time may be the same or different, and the sintering heat-holding stage may be performed in an inert gas or in a vacuum state.
[0047] For example, the heating rate during each sintering step is 0.5 to 5° C. / min, more preferably 1 to 4° C. / min, and the heating rates in each heating step may be the same or different.
[0048] According to an embodiment of the present invention, between two adjacent sintering and heat-retaining processes, the next temperature-raising and heat-retaining process may be performed directly after the previous sintering and heat-retaining stage is completed, or the previous sintering and heat-retaining stage may be cooled first and then the next temperature-raising and heat-retaining process may be performed. The cooling temperature is not limited as long as it is lower than the temperature of the previous sintering and heat-retaining stage, and the number of cooling stages is not particularly limited as long as it reaches the required cooling temperature. That is, any random process can be provided between two adjacent sintering and heat-retaining processes. For example, after the previous sintering and heat-retaining stage is completed, 1 to 10 stages of cooling are first performed, and then the next temperature-raising and heat-retaining process is performed, and the cooling temperatures of the 1 to 10 stages may be the same or different.
[0049] In order to ensure production efficiency, the sintering and heat-retaining stage is preferably controlled within 10 sets.
[0050] In the present invention, the above-mentioned three or more stages of sintering and heat retention process can be used to realize uniform distribution of elements such as Cu, Ga, and Al, and this sintering mode helps elements such as Cu, Ga, and Al to segregate from the grain boundary phase to the main phase crystal grains.
[0051] According to an embodiment of the present invention, in step (d), the aging treatment is performed after the sintering treatment is cooled. Illustratively, the aging treatment includes cooling to room temperature after the sintering is completed, and then performing a temperature rise treatment.
[0052] Preferably, the ageing treatment is selected from a primary ageing treatment or a secondary ageing treatment.
[0053] Preferably, the conditions of the primary aging treatment are an aging treatment temperature of 500-700°C and a heat-retention time of 240-420 min. Preferably, the secondary aging treatment includes a first aging treatment in which the temperature is increased to 800-950°C and the heat-retention time is 180-300 min, and a second aging treatment in which the temperature is increased to between 450-600°C after cooling to 200°C or lower and the heat-retention time is 240-360 min.
[0054] According to an embodiment of the present invention, after the sintering process, a diffusion treatment may also be performed.
[0055] Preferably, the diffusion treatment includes applying a diffusion material to the magnet surface, and performing a vacuum heating diffusion treatment, a diffusion cooling and a diffusion aging treatment.
[0056] Preferably, the diffusion material is at least one selected from the group consisting of pure metals of Dy and / or Tb, hydrides of Dy and / or Tb, oxides of Dy and / or Tb, hydroxides of Dy and / or Tb, and alloys of Dy and / or Tb, such as fluorides of Dy and / or Tb, and is illustratively Dy metal.
[0057] Preferably, the diffusion treatment can be carried out by using a method such as vacuum deposition, magnetron sputtering, coating or embedding.
[0058] Preferably, the temperature of the vacuum thermal diffusion treatment is 850 to 950° C., and the time of the vacuum thermal diffusion treatment is 10 to 30 hours.
[0059] Preferably, the temperature of the diffusion cooling is less than 100°C.
[0060] Preferably, the temperature of the diffusion aging treatment is 450 to 600° C., and the time of the diffusion aging treatment is 4 to 8 hours.
[0061] According to embodiments of the present invention, the billet may also be machined to a target size after the sintering process and before the diffusion treatment.
[0062] According to an embodiment of the present invention, after the sintering process and before the diffusion process, the magnets are explicitly cleaned after machining the billet to the target size to remove any machining debris, machining cutting fluid residues or machining adhesives on the magnet surface.
[0063] According to an embodiment of this aspect, the cleaning process before diffusion can be, but is not limited to, ultrasonic cleaning with pure water and pickling, and the acid can be, but is not limited to, nitric acid, sulfuric acid, citric acid, etc.
[0064] The present invention further provides an application of the above neodymium iron boron magnet for use in motor applications.
[0065] The present invention further provides a motor including the above magnet.
[0066] The present invention further provides applications of the above motor, preferably, the above motor can be applied to new energy vehicles and energy-saving home appliances.
[0067] Beneficial Effects of the Invention: The present invention makes it possible to obtain magnets with relatively high Br and Hcj by adjusting the component compounding ratios and distribution in the magnet of elements such as Cu, Ga, and Al, as well as the grain size of the crystal grains. The sintering method provided by the present invention, i.e., three or more sintering and temperature-keeping stages and the temperature-raising stage before temperature-keeping, not only ensures sufficient sintering and density improvement of the main phase crystal grains and grain boundary phase of the magnet, but also suppresses abnormal growth of the main phase crystal grains and prevents the oriented and ordered crystal grains from deflecting during sintering, ensures the degree of orientation of the magnet, and significantly improves the Br of the magnet.
[0068] Within the range of the Cu, Ga and Al atomic concentration ratios of the present application (i.e., 1≦[Cu2] / [Cu1]<2, 1≦[Ga2] / [Ga1]<2, 1<[Al2] / [Al1]<2), R2(Fe,M) 14 When the B structure is formed, the M concentration at the grain boundary between the main phase crystal grains is relatively low, and a relatively high Hcj is obtained while still maintaining a relatively high remanence. After the diffusion process, the Hcj improvement effect is significant, and the diffusion of Tb can improve Hcj to 880kA / m or more, and the diffusion of Dy can improve Hcj to 480kA / m or more. [Brief description of the drawings]
[0069] [Figure 1] FIG. 2 is a diagram showing Cu distribution in the magnet of Example 1. [Diagram 2] FIG. 4 is a diagram showing Cu distribution in the magnet of Comparative Example 1.
[0070] [Mode for carrying out the invention] The technical solution of the present invention will be described in more detail below with reference to specific examples. It should be understood that the following examples are merely illustrative and explanatory of the present invention and should not be construed as limiting the scope of the claims of the present invention. Any technology realized based on the above content of the present invention is included in the scope of the claims of the present invention.
[0071] Unless otherwise specified, all materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0072] Examples 1-2 A method for producing a neodymium iron boron magnet, the method including the following steps.
[0073] (a) Raw materials were prepared according to the target components of the magnet in Table 1 below, and smelted using a vacuum induction smelting furnace under Ar gas atmosphere protection. The molten liquid was cast into a quench roll with a rotation speed of 33 rpm so as to make the casting temperature 1420°C (i.e., strip casting process), and a neodymium iron boron alloy sheet was produced, and the average thickness of the target alloy sheet was 0.22 mm.
[0074] [Table 1]
[0075] (b) The alloy sheet was coarsely crushed by hydro-fracturing process to obtain powder, and zinc stearate, the mass of which was 0.1wt% of the raw material, was added to the powder as a lubricant and mixed for 60min. The mixed material was finely crushed by a fluidized bed jet mill, and nitrogen gas was used as the grinding gas. By adjusting the equipment parameters such as the rotation speed of the grading wheel and the grinding pressure, a jet mill powder with a target particle size SMD=2.5μm (i.e., alloy powder) was obtained, and the X90 / X10 was 4.2.
[0076] (c) Zinc stearate, the mass of which is 0.2 wt% of the raw materials, is further added as a lubricant to the jet mill powder of the target particle size obtained by production, and mixed for 120 min. After thorough mixing, the mixture is pressed into a billet with a magnetizing magnetic field strength of 2 T, and then isostatically pressed with an isostatic press at a pressure of 180 MPa for 15 s to improve the density of the billet and make it have a density of 4.3 g / cm. 3 The billet was obtained.
[0077] (d) The billet was placed in a sintering furnace, heated in a vacuum atmosphere, and then heated at 150°C and 260°C for 100 min each to remove the lubricant, then heated at 600°C and 900°C for 90 min each to remove the gases, and then subjected to the three-stage sintering and heat-retention process shown in Table 2 below. After the third sintering and heat-retention stage was completed, the material was cooled directly to room temperature to obtain a sintered body. The specific three-stage heating and heat-retention sintering process is shown in Table 2 below, and after each sintering and heat-retention stage was completed, the material was heated directly to the next heating process.
[0078] [Table 2]
[0079] (e) Secondary aging treatment: The above sintered body was taken, heated to 900°C and kept at that temperature for 180 minutes, then cooled to 200°C, and then further heated to 530°C and kept at that temperature for 240 minutes. After the temperature keeping was completed, the body was cooled to room temperature to obtain a magnet after aging treatment.
[0080] (f) The magnets after aging treatment were processed into sample columns with a standard of φ10-10, and the magnet performance was measured using a BH device. The specific magnetic performance test results are shown in Table 3.
[0081] [Table 3]
[0082] The vertically oriented surface of the magnets manufactured in Examples 1 and 2 was polished, and the size of the magnet crystal grains was confirmed by a scanning electron microscope (SEM). The average crystal grain size in the field of view (×2000 magnification) was defined by Image-Pro Plus software analysis, and the grain size of the largest crystal grain in the field of view was defined as the maximum crystal grain size. The number of crystal grains was counted in the ×2000 magnification field of view, and the field area was divided by the number of crystal grains to obtain the unit crystal grain area. The grain size of the crystal grains was calculated using the circle area formula to obtain the average grain size. The grain with the largest area in the field of view was taken, and the grain size of the crystal grain was calculated using the circle area formula to obtain the maximum grain size. The test results are shown in Table 4.
[0083] The distribution of each component in the magnet was analyzed and confirmed using a field emission electron probe microanalyzer (FE-EPMA) (JEOL, 8530F). Line scanning was performed to pass through the main phase crystal grains, the double grain boundaries, and the triangular grain boundaries to confirm and analyze the differences in the distribution concentrations of elements such as Cu, Ga, and Al in the above areas. The atomic concentrations of Cu, Ga, and Al at a position 0.5 μm inside the main phase crystal grains from the double grain boundaries were defined as [Cu1], [Ga1], and [Al1], respectively, and the atomic concentrations of Cu, Ga, and Al at the center position of the double grain boundary between two main phase crystal grains were defined as [Cu2], [Ga2], and [Al2], respectively. The average ratio of five pairs of adjacent main phase crystal grains and double grain boundaries within the field of view was defined as [Cu2] / [Cu1], and it was confirmed whether the Cu element was relatively uniformly distributed in the main phase crystal grains and the double grain boundaries based on the concentration ratio of the two. In the triangular grain boundaries, the area where the Cu element concentration satisfies [Cu3] / [Cu1] ≥ 2 was defined as the Cu-rich area, and the ratio of the area of the Cu-rich area to the total area of the grain boundary phase was calculated using Image-Pro Plus software analysis. The relative distribution of Ga and Al and the area occupancy of the enriched areas were calculated using the same test analysis method.
[0084] The distribution and structural characteristics of Cu, Ga, and Al measured by the above analytical methods are shown in Table 4 below.
[0085] [Table 4]
[0086] FIG. 1 shows the distribution of Cu in the magnet of Example 1. As can be seen from FIG. 1, Cu is distributed relatively uniformly in the surface layers of the main phase crystal grains and in the two-grain boundaries, and although Cu-rich regions are present in the triangular grain boundaries, the area occupancy of the Cu-rich regions is relatively small, and the concentration of Cu in the triangular grain boundaries is also relatively low.
[0087] Comparative Examples 1-2 (a) Raw materials were prepared according to the target components of the magnet in Table 5 below, and manufactured using a strip casting process to obtain a neodymium-iron-boron alloy sheet, with the average thickness of the target alloy sheet being 0.22 mm.
[0088] [Table 5]
[0089] Using the same process as in Examples 1 and 2, the alloy sheet was pulverized and milled, the alloy powder was press-molded, and sintered according to the three-stage heating and heat-retention sintering process in Table 6 below. After each sintering and heat-retention stage was completed, the temperature was directly increased to perform the next heating process, and after the third heat-retention stage was completed, the temperature was cooled to room temperature, and a sintered body was manufactured.
[0090] Secondary aging treatment: The above sintered body was taken, heated to 900°C and kept at that temperature for 180 minutes, then cooled to 200°C, and then further heated to 530°C and kept at that temperature for 240 minutes. After the temperature keeping was completed, it was cooled to room temperature to obtain a magnet after aging treatment.
[0091] [Table 6]
[0092] The magnetic properties were tested according to the above magnetic properties test method, and the test results are shown in Table 7. The magnet grain size test and element distribution test were also performed according to the above magnet grain size test and element distribution method, and the results are shown in Table 8.
[0093] [Table 7]
[0094] [Table 8]
[0095] *Since Ga and Al were not added to the magnet design components of Comparative Example 2, "--" indicates that the component concentrations were not compared.
[0096] FIG. 2 shows the distribution of Cu in the magnet of Comparative Example 1. As can be seen from FIG. 2, the degree of Cu enrichment in the surface layers of the main phase crystal grains and the two-grain boundaries is relatively low, but compared with FIG. 1, the relative concentration at the two-grain boundaries is still relatively high, and the Cu-rich areas at the triangular grain boundaries have obviously increased and the area occupancy rate is relatively high, i.e., Cu is highly enriched at the triangular grain boundaries.
[0097] Comparing Examples 1-2 and Comparative Examples 1-2, the Br of Comparative Example 2 was slightly improved compared to the Br of Examples 1-2, but the coercive force Hcj was significantly reduced and the squareness was also significantly reduced. When each component element of the magnet is within the range of the present invention, the overall performance of its Br and Hcj is superior, and it has an excellent squareness Hk / Hcj, ensuring a stable magnetic field output of the magnet.
[0098] Example 3 The difference between Example 3 and Example 1 was that the sintering process was carried out according to the three-stage temperature increase and temperature retention sintering process in Table 9 below, and after each stage of sintering and temperature retention was completed, the material was cooled to 900°C, and then the next stage of temperature increase was performed in step (d).
[0099] [Table 9]
[0100] Comparative Example 3 The difference between Comparative Example 3 and Example 1 was that the sintering process was carried out according to the two-stage temperature increase and temperature retention sintering process in Table 10 below, and after the first stage of temperature retention was completed, the material was cooled to 400°C, and then a second stage of temperature increase was carried out in step (d).
[0101] [Table 10]
[0102] The magnets produced in Example 3 and Comparative Example 3 were subjected to magnetic performance tests and magnet crystal grain size and element distribution analyses. The results of the magnetic performance tests are shown in Table 11, and the crystal grain size and element distribution are shown in Table 12.
[0103] [Table 11]
[0104] [Table 12]
[0105] Comparing Example 3 with Comparative Example 3, the use of the temperature-rising and temperature-holding sintering process of the present invention has a shorter period and better magnetic performance than the conventional two-stage sintering process, effectively inhibits the abnormal growth of magnet crystal grains, and realizes uniform distribution of Cu, Ga, and Al elements in the main phase crystal grains and the two-grain grain boundaries, and reduces their concentration in the triangular grain boundaries.
[0106] Compared to Example 1, Example 3 increases the number of steps in which, after each temperature increase and maintenance, the material is cooled to below 900°C after each temperature maintenance step, and then the material is heated to the next temperature step. By using a sintering process that separates heating and cooling into three stages, it is possible to more effectively suppress abnormal growth of magnet crystal grains and slightly improve magnet performance.
[0107] Example 4 The sintered and aged magnets of Example 3 were taken and processed into sheet products with a length of 20 mm, a width of 20 mm and a thickness of 5 mm, and a thin film of metallic Dy was added to the magnet surface by a dip coating process, and then the magnet was subjected to a diffusion treatment at 900°C for 15 hours, and after the diffusion temperature was cooled to below 100°C, the magnet was further heated to 500°C for an aging treatment for 5 hours. The final magnets were subjected to a magnetic performance test, and the test results are shown in Table 13 below.
[0108] Comparative Example 4 The sintered and aged magnet of Comparative Example 3 was taken and processed through the same diffusion treatment process as in Example 4, i.e., the magnet was processed into a sheet product with a length of 20 mm, a width of 20 mm and a thickness of 5 mm, a thin film of metallic Dy was added to the magnet surface through a dip coating process, and then the magnet was diffused at 900°C for 15 hours, cooled to a diffusion temperature below 100°C, and then further heated to 500°C for aging treatment for 5 hours. The final magnet was subjected to a magnetic performance test, and the test results are shown in Table 13 below.
[0109] [Table 13]
[0110] In Table 13, ΔBr and ΔHcj respectively indicate the Br amplification and Hcj amplification of Example 4 relative to Example 3, and the Br amplification and Hcj amplification of Comparative Example 4 relative to Comparative Example 3.
[0111] Comparing the results of Example 4 and Comparative Example 4, using the same diffusion process, the Hcj amplification of the magnet diffusion produced by the method of the present invention is better, the final magnet performance is better, and its texture is more suitable for diffusion.
[0112] The above describes the embodiments of the present invention by way of example. However, the scope of the claims of the present invention is not limited to the above embodiments. Any modifications, equivalent replacements, improvements, etc. made by those skilled in the art without departing from the spirit and principles of the present invention are also included in the scope of the claims of the present invention.
Claims
1. A high performance neodymium iron boron magnet, The magnet is R 2 (Fe, M) 14 The alloy comprises main phase crystal grains and a grain boundary phase having a B structure, the grain boundary phase comprising a double grain boundary between two main phase crystal grains and a triangular grain boundary formed by gaps between three or more main phase crystal grains, wherein M comprises Cu, Ga and / or Al, and R represents at least one rare earth element including Nd. High performance neodymium iron boron magnets.
2. The average grain size of the main phase crystal grains of the magnet is 1.8 to 8 μm, preferably 2.5 to 6 μm; Preferably, the atomic concentration of Cu in the adjacent main phase crystal grains is [Cu 1 ], and the atomic concentration of Cu at the two grain boundaries is set to [Cu 2 ], and 1≦[Cu 2 ] / [Cu 1 ]<2, Preferably, the triangular grain boundaries in the magnet include Cu-rich regions, and the atomic concentration of Cu at the triangular grain boundaries is defined as [Cu 3 ] and set it to [Cu 3 ] / [Cu 1 ] ≧2; Preferably, the ratio of the area of the Cu-rich region of the triangular grain boundary to the total area of the grain boundary phase is <5%.
2. The magnet of claim 1 .
3. The atomic concentration of Ga in the adjacent main phase crystal grains is defined as [Ga 1 ] and the Ga atomic concentration at the two grain boundaries is set to [Ga 2 ], and 1≦[Ga 2 ] / [Ga 1 ]<2, Preferably, the triangular grain boundaries in the magnet include Ga-rich regions, and the atomic concentration of Ga at the triangular grain boundaries is [Ga 3 ] and set it to [Ga 3 ] / [Ga 1 ] ≧2; Preferably, the grain boundary phase of the Ga-rich region is a non-ferromagnetic phase, and the ratio of the area of the Ga-rich region of the triangular grain boundary to the total area of the grain boundary phase is <5%.
3. A magnet according to claim 1 or 2.
4. The atomic concentration of Al in the adjacent main phase grains is defined as [Al 1 ], and the atomic concentration of Al at the two grain boundaries is set to [Al 2 ], and 1 < [Al 2 ] / [Al 1 ]<2, Preferably, the triangular grain boundaries in the magnet include Al-rich regions, and the atomic concentration of Al at the triangular grain boundaries is defined as [Al 3 ] and set it to [Al 3 ] / [Al 1 ] ≧2; Preferably, the ratio of the area of the Al-rich region of the triangular grain boundary to the total area of the grain boundary phase is <5%; Preferably, adjacent main phase grains refer to main phase grains adjacent to a two-grain boundary. The magnet according to any one of claims 1 to 3.
5. The high-performance neodymium iron boron magnet further contains a transition metal element, which is at least one of Mn, Si, Zr, Ti, and Nb. The magnet according to any one of claims 1 to 4.
6. The high-performance neodymium iron boron magnet is 100% by mass, R of 27 to 35% and 0.8 to 1.2 wt% B; 0 to 3.0 wt % Co; 0.1 to 0.6 wt % Cu; 0.1 to 0.8 wt % Ga; 0 to 1.0 wt % Al; 60 to 72 wt % T; wherein R is at least one rare earth element including Nd, and T includes Fe and other transition metal elements as well as unavoidable impurity elements, the transition metal elements having the meanings set forth in claim 5; A magnet according to any one of claims 1 to 5.
7. A method for producing a magnet according to any one of claims 1 to 6, comprising the steps of: (a) a smelting process in which the components of the magnet are melted, cast, and cooled to form an alloy sheet; (b) a milling process in which the alloy sheet is pulverized into alloy powder; (c) a press molding process in which the alloy powder is press molded under the action of a magnetic field to obtain a billet; (d) sintering the billet, aging, and manufacturing the billet to obtain a NdFeB magnet. A method comprising:
8. In step (b), the SMD grain size of the alloy powder is 1.8-8 μm, preferably 2.5-6 μm, and X90 / X10≦4.5; Preferably, in step (d), the sintering process has three or more sintering temperature-keeping stages and pre-sintering temperature-keeping heating stages, illustratively 3 to 10 stages, the temperature of the sintering temperature-keeping stage is 950 to 1200 ° C, preferably 980 to 1070 ° C, and the temperature-keeping time of each stage is 20 to 120 min; Preferably, the heating rate during each sintering step is 0.5 to 5° C. / min, more preferably 1 to 4° C. / min; Preferably, between each two adjacent sintering and heat-retaining processes, the next temperature-raising and heat-retaining process is directly carried out after the previous sintering and heat-retaining process is completed, or the previous sintering and heat-retaining process is first cooled and then the next temperature-raising and heat-retaining process is carried out after the previous sintering and heat-retaining process is completed, that is, any random process can be provided between each two adjacent sintering and heat-retaining processes.
8. The method of claim 7.
9. The aging treatment is selected from a primary aging treatment or a secondary aging treatment, Preferably, the conditions of the primary aging treatment are that the aging treatment temperature is 500 to 700° C. and the heat retention time is 240 to 420 min. Preferably, the secondary aging treatment includes: performing a first aging treatment by increasing the temperature to 800 to 950°C and a heat-retention time of 180 to 300 min; and performing a second aging treatment by cooling to 200°C or less and then increasing the temperature to between 450 to 600°C and a heat-retention time of 240 to 360 min; Preferably, after the sintering process, a diffusion treatment may also be carried out, Preferably, the diffusion treatment includes applying a diffusion material to a magnet surface, and performing a vacuum heating diffusion treatment, a diffusion cooling treatment, and a diffusion aging treatment; Preferably, the diffusion material is at least one selected from the group consisting of pure metals of Dy and / or Tb, hydrides of Dy and / or Tb, oxides of Dy and / or Tb, hydroxides of Dy and / or Tb, and fluoride alloys of Dy and / or Tb; 9. The method according to claim 7 or 8.
10. Application of the magnet according to any one of claims 1 to 6 for use in a motor, Preferably, it is used in new energy automobiles or energy-saving home appliances; 13. An application characterized in that
Citation Information
Patent Citations
Sintering method for neodymium iron boron magnet
CN103572083A
Preparation method for neodymium iron boron materials
CN105140012A
Sintering method of neodymium-iron-boron magnet
CN106252012A
Sintering method for reducing carbon content of NdFeB magnet
CN106601459A
Low-temperature sintering method for preparing neodymium-iron-boron magnet
CN106623916A